Pengaruh Komunikasi Pemasaran, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Krupuk Pratama Di Sidoarjo - Qur’Ana, Dinda Ucik; Hariasih, Misti; Sari, Dewi Komala (Universitas Islam Kadiri, 2025)
This study aims to determine the Effect of Marketing Communication, Price and Service Quality on Consumer Satisfaction of Krupuk Pratama. This study uses a quantitatve approach with the population being krupuk pratama consumers. The sampling technique in this study was carried out using a non probability sampling method with a purposive sampling technique with a total of 100 respondents. The collection technique was by distributing questionnaires and answers were measured using a likert scale. The analysis technique in this study used the PLS-SEM method with the help of SmartsPLS 3.0 software. The results of this study prove that marketing communication has an effect on krupuk pratama consumer satisfaction, and servive quality has an effect on krupuk pratama consumer satisfaction.